The changing characteristics of patients infected with chronic hepatitis C virus from 2014 to 2019: Real‐world data from the German Hepatitis C‐Registry (DHC‐R). Issue 10 (12th August 2021) - Hüppe, Dietrich; Stoehr, Albrecht; Buggisch, Peter; Mauss, Stefan; Klinker, Hartwig; Teuber, Gerlinde; Hidde, Dennis; Lohmann, Kristina; Bondin, Mark; Wedemeyer, Heiner
Abstract: The number of patients diagnosed with hepatitis C virus (HCV) is markedly higher than the number initiating treatment indicating gaps in the care cascade, likely centred around reaching at‐risk populations. Understanding changing characteristics of patients with HCV allows for targeted programs that increase linkage to care. We investigated changes in demographic and clinical characteristics of patients registered in the German Hepatitis C‐Registry (DHC‐R) from 1 January 2014 to 31 December 2019. The DHC‐R is an ongoing, noninterventional, multicentre, prospective, observational cohort registry including 327 German centres. Patient characteristics were analysed over time in 7 phases for all patients completing a screening visit. Overall, 14, 357 patients were enrolled. The percentage of treatment‐naïve/non‐cirrhotic patients increased from 34.4% in phase 1 (1 January–31 December 2014) to 68.2% in phase 7 (1 August–31 December 2019). The proportion of migrants, alcohol users, people who inject drugs, and those receiving opiate substitution therapy increased in later registry phases. Most patients (60.1%) were receiving comedication at baseline. The most prescribed comedications were drugs used to treat opioid dependence which increased from 9.2% in phase 1 to 24.0% in phase 7. The patients' mean age decreased from 52.3 years in phase 1 to 48.7 years in phase 7. From 2014 to 2019, the proportion of at‐risk patients enrolling in the registry increased. To eliminate viral hepatitis as a major public health threat, a continued commitment to engaging underserved populations into the HCV care cascade is needed.